Optimization of Facility Layout Problems Using Genetic Algorithm - Suharjito Suharjito; Muslim Muslim (Syntax Literate, 2023)
The facility layout problem (FLP) is one of the most important classic industrial engineering and production management problems that have attracted the attention of many researchers over the last few decades. Poor production facility layout planning can result in additional operational costs; one of them is the cost of material handling. Although crucial, FLP is a challenging issue to resolve. A unique method is needed depending on the constraint, case study, and layout type. This research was conducted in order to improve the existing layout of PT. XYZ to minimize material handling costs. The layout type in this case is the Open-field layout problem (OFLP). A genetic algorithm is proposed to optimize the layout. The result is 18.1% material handling costs can be reduced.